2007
DOI: 10.1017/s1481803500015475
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with delay to emergency department presentation, antibiotic usage and admission for human bite injuries

Abstract: Objectives: Evidence and consensus on best practices on the management of human bite injuries is lacking. Our objective was to identify factors that are associated with delay to emergency department (ED) presentation, antibiotic usage and patient admission. Methods: We present a retrospective chart review of adults treated for human bites. Multivariable logistic regression models used demographic characteristics and bite circumstances and characteristics as factors associated with ED presentation more than 24 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 10 publications
0
10
1
1
Order By: Relevance
“…This finding is however contrary to a similar study conducted in Ghana where victims of human bite usually presented during the first two days of the injury [1]. Patients with human bite injury are often either intoxicated [2] or are known to their assailant [1] making the process of obtaining a reliable history especially about the aetiology difficult. In 2002, a study estimated the rate of infection secondary to human bite to be about 10% Perron et al [3].…”
Section: Introductioncontrasting
confidence: 62%
See 2 more Smart Citations
“…This finding is however contrary to a similar study conducted in Ghana where victims of human bite usually presented during the first two days of the injury [1]. Patients with human bite injury are often either intoxicated [2] or are known to their assailant [1] making the process of obtaining a reliable history especially about the aetiology difficult. In 2002, a study estimated the rate of infection secondary to human bite to be about 10% Perron et al [3].…”
Section: Introductioncontrasting
confidence: 62%
“…Studies have shown that human bites are more common among males [1] with the peak incidence between 18 and 78 years according to Merchant et al [2]. In a study of 388 patients with human bite by Merchant et al [2], 76.2% of patients presented to emergency within 12 hrs of injury [2]. This finding is however contrary to a similar study conducted in Ghana where victims of human bite usually presented during the first two days of the injury [1].…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Bazı yazarlar bütün insan ısırığı yaralanmalarının yüksek enfeksiyon riski taşıdığına ve antibiyotik profilaksisine alınmasının uygun olduğuna inanırken diğerleri kapalı yumruk yaralanmaları gibi özel durumlarda profilaksi yapılmasının gerekli Resim 1. İnsan ısırığına bağlı, sağ yanak bölgesinde 3x3 cm boyutlarında, hiperemik, ekimotik, üzerinde diş izleri bulunan ve yer yer kurutlanmaya başlamış lezyonun yandan görünümü olduğunu savunurlar (9,10). Medeiros ve Saconato bir derlemelerinde profilaktik antibiyotik kullanımının kedi ve köpek ısırıklarında infeksiyon hızında bir azalma sağlamazken insan ısırıklarında anlamlı bir düşüşe sebep olduğu sonucuna vardılar (11).…”
Section: Discussionunclassified
“…Studies have suggested that closed fist injuries account for around 50% of human bite injuries to the hand [17]. The metacarpophalangeal joint is at risk of injury.…”
Section: Pathophysiologymentioning
confidence: 99%